2009
DOI: 10.1037/a0016161
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cortical gray matter atrophy may be overestimated in the healthy aging brain.

Abstract: Prevailing opinion holds that normal brain aging is characterized by substantial atrophy of cortical gray matter. However, this conclusion is based on earlier studies whose findings may be influenced by the inclusion of subjects with subclinical cognitive disorders like preclinical dementia. The present magnetic resonance imaging study tested this hypothesis. Cognitively healthy subjects (mean age 72 years, range 52-82) who remained cognitively stable over a 3-year period were compared to subjects with signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
(61 reference statements)
1
52
3
2
Order By: Relevance
“…For example, if patients aged 60 and older had general atrophic brain changes with a decrease in the size of the temporal lobes of up to 5%, it was considered natural age-related changes and equal to normal [12,36,38]. The calculation of volume changes of the whole temporal lobe of the brain gives more accurate results of the severity of atrophic changes than calculation of atrophic changes of only the hippocampus, which is confirmed by studies of other authors [39].…”
Section: Methodssupporting
confidence: 68%
“…For example, if patients aged 60 and older had general atrophic brain changes with a decrease in the size of the temporal lobes of up to 5%, it was considered natural age-related changes and equal to normal [12,36,38]. The calculation of volume changes of the whole temporal lobe of the brain gives more accurate results of the severity of atrophic changes than calculation of atrophic changes of only the hippocampus, which is confirmed by studies of other authors [39].…”
Section: Methodssupporting
confidence: 68%
“…As a consequence, cross sectional studies are more often conducted in order to estimate age-related changes, although they might produce inconsistent results when compared to longitudinal analyses (Pfefferbaum and Sullivan 2015). Indeed, the cross-sectional approach is easier to implement, but it suffers from major flaws including potential cohort bias and the influence of elder individuals at the presymptomatic stage of a neurodegenerative disorder which may cause an overestimation of the age effect (Burgmans et al, 2009). …”
Section: Studying Aging: Methodological Considerationsmentioning
confidence: 97%
“…Some have even suggested that cortical decline in aging is caused by undetected disease and is not a feature of normal aging (Burgmans et al, 2009). An important implication of the apparent temporal gap between detectable cerebral and cognitive expression of dementia is that cases with undetected disease in presumably normal samples could bias inferences about normal brain aging (Sliwinski and Buschke, 1999).…”
Section: Normal Aging Versus Alzheimer’s Disease: How To Tell the mentioning
confidence: 99%